POLITICAL ECONOMY OF FINANCIALIZATION: KEY ISSUES AND APPROACHES - GoltsmanК. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The present article investigates key issues and approaches to phenomenon of financialization in Western economies. Financialization tendency has been reflected in growing weight of finance in economy, increased impact of financial fraction of ruling class on economic policy, inversion of relationship between „real” and „financial” sectors and growing household indebtedness. It is argued that contrary to the position of mainstream economic theory, growth of finance should not be considered just a matter of economic deregulation and liberalisation. Focusing on critical theories of finance and Marxist political economy, we put forward a new framework for analysis of financialization trend. In the proposed approach, financialization is regarded as a complex constellation of economic, political and ideological transformations connected with recent shifts in class relations and capital accumulation in Western countries.